Collaborative Design-Build Initiative for Local Resiliency Building - Subasinghe, Chamila (2020)
Beyond communication barriers, local resiliency building with communities often challenges traditional trajectories of design-build. Without ambitious performance hurdles, two academic institutions from Australia and Thailand built rapport via their common love for Bamboo to level hierarchies between groups: architects, both social and professional. We used Bashō’s ‘self’- object nexus as depicted in ‘learn Bamboo from Bamboo’ haiku as a methodology (Haas, 1994). Although intercultural communication tends to create frictions that may lead to alienated efforts, we discovered that understanding scaffolded on reciprocal respect for culture of craft found in Bamboo could ease tensions toward ‘no-learning at all’ or reciprocity. However, through this project, we discovered that Bamboo could become an effective mode of communication through its value as interculturally understood landscape, artefact, technology, and relationship-building platform.